2010
DOI: 10.1007/s12583-010-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Progress and controversy in the study of HP-UHP metamorphic terranes in the West and Middle Central China orogen

Abstract: During the past ten years, various types of HP-UHP metamorphic rocks have been discovered in the South Altyn Tagh, the North Qaidam and the North Qinling (秦岭) in the West and Middle Central China orogen. The UHP rocks, as lentoid bodies in regional gneisses, include eclogite (garnet-bearing pyroxenite), garnet peridotite and various pelitic or felsic gneisses. There are many records of minerals and microstructures of exsolution indicate the UHP metamorphism, such as coesite (or its pseudomorph), diamond, exsol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 90 publications
0
18
0
1
Order By: Relevance
“…Cheng et al () considered ages of 494 ± 3 Ma for eclogite facies metamorphism based on whole‐rock+garnet+omphacite Lu‐Hf isochron dating of two eclogite samples. Several other studies have also suggested Late Cambrian to Early Ordovician ages for the HP to UHP eclogite facies metamorphism due to the continental subduction (Li et al, ; Liao et al, ; Liu, Yang, et al, ; Ratschbacher et al, ; Wang et al, ; Yu et al, ). The Cambrian metamorphic ages for the Tongbai orogen suggest that this orogen shares the same episode of continental collision with the Qinling orogen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cheng et al () considered ages of 494 ± 3 Ma for eclogite facies metamorphism based on whole‐rock+garnet+omphacite Lu‐Hf isochron dating of two eclogite samples. Several other studies have also suggested Late Cambrian to Early Ordovician ages for the HP to UHP eclogite facies metamorphism due to the continental subduction (Li et al, ; Liao et al, ; Liu, Yang, et al, ; Ratschbacher et al, ; Wang et al, ; Yu et al, ). The Cambrian metamorphic ages for the Tongbai orogen suggest that this orogen shares the same episode of continental collision with the Qinling orogen.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with the northward subduction of the North Qinling microcontinent beneath the Erlangping arc terrane in the Cambrian. The synchronous UHP eclogite facies metamorphism in the Qinling orogen provides robust evidence for continental deep subduction to the subarc depths (Liao et al, ; Liu et al, ; Liu, Yang, et al, ; Wang, Wu, Gao, Liu, et al, ; Wang, Wu, Gao, Zhang, et al, ; Yu et al, ). It is known that continental subduction for collisional orogeny leads to crustal thickening, which is evident in the Rocky Mountains, the Central Andes, and the Himalaya (e.g.…”
Section: Implications For the Tectonic Evolution Of The Tongbai Orogenmentioning
confidence: 99%
“…Examples of HT metamorphism are observed in the country rocks of the Beni Bousera (northern Morocco) and Ronda (southern Spain) massifs (Loomis, 1972), as well as in the limestones hosting the Pyrenean lherzolites (Goldberg and Leyreloup, 1990). However, several orogenic peridotites are associated with HP to UHP terranes, notably in the Central Alps (Alpe Arami, Cima di Gagnone, and Ulten peridotites), China (Dabie-Sulu, Qinling, and North Qaidam-Altyn-Tagh UHP metamorphic belts), the Western Gneiss Region (WGR) in Scandinavian Caledonides, and the Bohemian Massif in Central Europe Ernst, 1981;Ernst and Liou, 2008;Kotkova et al, 2011;Liou et al, 2002aLiou et al, ,b, 2009Liu et al, 2010;Reverdatto and Selyatitskii, 2005;Schmaedicke et al, 2010;Terry et al, 2000;van Roermund, 2009b;Zhang et al, 2005).…”
Section: Orogenic Peridotite Massifsmentioning
confidence: 99%
“…Considering the paleogeographic framework of eastern Gondwana, early Paleozoic metamorphic rocks, especially the ultrahigh/high- Chen et al, 2007Chen et al, , 2009Zhang et al, 2008;Song et al, 2006;Yu et al, 2013), the South Altyn (501-485 Ma; Zhang et al, 2005;Liu et al, 2012;Cao et al, 2013), the North Qinling orogen (ca. 511-480 Ma, Liu et al, 2010;Zhang et al, 2011;Wang et al, 2011;Cheng et al, 2011Cheng et al, , 2012ca. 440-424 Ma, Zhang et al, 2011), Sibumasu (ca.…”
Section: Early Palaeozoic Hp/uhp Metamorphism In Gondwana-derived Termentioning
confidence: 99%
“…501-485 Ma; Zhang et al, 2005;Liu et al, 2012;Cao et al, 2013), the North Qinling orogen (ca. 511-480 Ma; Liu et al, 2010;Zhang et al, 2011;Cheng et al, 2011Cheng et al, , 2012Wang et al, 2011;ca. 440-424 Ma, Zhang et al, 2011), Sibumasu (ca.…”
Section: Early Palaeozoic Hp/uhp Metamorphism In Gondwana-derived Termentioning
confidence: 99%